HCI models, theories, and frameworks toward a multidisciplinary science - Carroll, John M. (John Millar), 1950- (San Francisco, Calif. : Morgan Kaufmann, 2003)
Finallya thorough pedagogical survey of the multidisciplinary science of HCI. Human-Computer Interaction spans many disciplines, from the social and behavioral sciences to information and computer technology. But of all the textbooks on HCI technology and applications, none has adequately addressed HCI's multidisciplinary foundationsuntil now. HCI Models, Theories, and Frameworks fills a huge void in the education and training of advanced HCI students. Its authors comprise a veritable house of diamondsinternationally known HCI researchers, every one of whom has successfully applied a unique scientific method to solve practical problems. Each chapter focuses on a different scientific analysis or approach, but all in an identical format, especially designed to facilitate comparison of the various models. HCI Models, Theories, and Frameworks answers the question raised by the other HCI textbooks: How can HCI theory can support practice in HCI? * Traces HCI research from its origins * Surveys 14 different successful research approaches in HCI * Presents each approach in a common format to facilitate comparisons * Web-enhanced with teaching tools at http://www.HCImodels.com *Contributors are leading researchers in the field of Human-Comptuter Interaction *Fills a major gap in current literature about the rich scientific foundations of HCI *Provides a thorough pedogological survey of the science of HCI.
Introduction: Toward a multidisciplinary science of human-computer interaction / John M. Carroll -- Design as applied perception / Colin Ware -- Motor behavior models for human-computer interaction / I. Scott MacKenzie -- Information processing and skilled behavior / Bonnie E. John -- Notational systems : the cognitive dimensions of notations framework / Thomas Green -- Users' mental models : the very ideas / Stephen J. Payne -- Exploring and finding information / Peter Pirolli -- Distributed cognition / Mark Perry -- Cognitive work analysis / Penelope M. Sanderson -- Common ground in electronically mediated communication : Clark's theory of language use / Andrew Monk -- Activity theory / Olav W. Bertelsen, Susanne Bodker -- Applying social psychology theory to the problems of group work / Robert E. Kraut -- Studies of work in human-computer interaction / Graham Button -- Upside-down [inverted A]s and algorithms : computational formalisms and theory / Alan Dix -- Design rationale as theory / John M. Carroll, Mary Beth Rosson.
Includes bibliographical references (p. 475-519) and index.
Keywords: Human-computer interaction; Electronic books